A user-centred social commitment model for location sharing applications in the family life domain. (27th March 2020) - Kayal, Alex; Brinkman, Willem-Paul; Neerincx, Mark A.; Riemsdijk, M. Birna Van
Mobile location-sharing technology is used increasingly by parents to know where their children are. It is our aim to make such technology more flexible in adapting to the particular social context in which it operates. We propose to realise this by allowing users to specify norms that govern the respective social contexts, to which the application should adapt at run-time to provide tailored support. The challenge we address in this paper is the development of a normative model tailored for mobile applications that support location sharing in family life. The novelty of our work lies in the fact that we employ empirical user-centred design methods and techniques for developing the model in an iterative and 'bottom-up' way. This results in two main contributions: 1) a normative model, specifically a social commitment model, for family life location sharing applications shown to be useful and usable, and 2) a demonstration of how user-centred design can be employed to develop a normative model for social applications.